Navigating the inclusive and sustainable energy transitions in South Asia: Progress, priorities and stakeholder perspectives - Asif, Muhammad; Imran Khan, Muhammad; Pandey, Asha (Energy conversion and management, 2024)
•Analyzes South Asia’s energy trilemma balancing energy access, security and sustainability.•Focuses on four major regional countries: India, Pakistan, Bangladesh, and Sri Lanka.•Identifies major challenges as lack of energy access, unreliable gird, and unaffordable prices.•Explores the prospects of renewable energy as the key toward a sustainable energy transition.•Presents stakeholder perspectives on crucial dynamics of energy transition. To address the faced challenges – i.e. rapidly growing energy needs, depleting fossil fuel reserves, surging energy prices, risks to security of supplies, and climate change – the World is targeting a sustainable energy transition. This energy transition is primarily propelled by a global decarbonization drive. South Asia, a developing region housing over 23% of the global population, faces the additional challenge of serious energy deprivation. The subject of energy transition has not been explored in the South Asian context in terms of drivers, challenges, and prospects. This paper investigates the prospects of sustainable energy transition in South Asia in terms of resources, consumption trends, and challenges encountered by countries in the region, particularly India, Bangladesh, Pakistan, and Sri Lanka. It also examines the sustainable and renewable energy options for the region. An original stakeholder survey provides salient behavioral insights into awareness, attitudes and opinions shaping societal response to energy transition. The findings of the study highlight the serious energy security issues faced by the region in terms of lack of access, inconsistent supplies, unreliable grids, and high energy prices. Renewables like solar energy, wind power, and hydropower have the potential to propel regional countries to energy and environmental sustainability. “Lack of consistent policies and regulations”, “lack of political will” and “lack of investment” are found to be the three most important challenges to the energy transition.